High risk clinical characteristics for subarachnoid haemorrhage in patients with acute headache: prospective cohort study. (28th October 2010) - Perry, Jeffrey J; Stiell, Ian G; Sivilotti, Marco L A; Bullard, Michael J; Lee, Jacques S; Eisenhauer, Mary; Symington, Cheryl; Mortensen, Melodie; Sutherland, Jane; Lesiuk, Howard; Wells, George A
Abstract : Objective To identify high risk clinical characteristics for subarachnoid haemorrhage in neurologically intact patients with headache. Design Multicentre prospective cohort study over five years. Setting Six university affiliated tertiary care teaching hospitals in Canada. Data collected from November 2000 until November 2005. Participants Neurologically intact adults with a non-traumatic headache peaking within an hour. Main outcome measures Subarachnoid haemorrhage, as defined by any of subarachnoid haemorrhage on computed tomography of the head, xanthochromia in the cerebrospinal fluid, or red blood cells in the final sample of cerebrospinal fluid with positive results on angiography. Physicians completed data collection forms before investigations. Results In the 1999 patients enrolled there were 130 cases of subarachnoid haemorrhage. Mean (range) age was 43.4 (16-93), 1207 (60.4%) were women, and 1546 (78.5%) reported that it was the worst headache of their life. Thirteen of the variables collected on history and three on examination were reliable and associated with subarachnoid haemorrhage. We used recursive partitioning with different combinations of these variables to create three clinical decisions rules. All had 100% (95% confidence interval 97.1% to 100.0%) sensitivity with specificities from 28.4% to 38.8%. Use of any one of these rules would have lowered rates of investigation (computed tomography, lumbar puncture, or both) from the current 82.9% to between 63.7% and 73.5%. Conclusion Clinical characteristics can be predictive for subarachnoid haemorrhage. Practical and sensitive clinical decision rules can be used in patients with a headache peaking within an hour. Further study of these proposed decision rules, including prospective validation, could allow clinicians to be more selective and accurate when investigating patients with headache.